Mengoptimalkan Window Ligthing untuk Foto Potret dengan Menggunakan Kamera DSLR 1000D dan 60D - Nofria Doni Fitri; r hadapiningrani kusumohendrarto (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2018)
Photography is a visual language that prioritizes the role of light. In photography there are several shooting formats, one of which is portrait or shooting vertically. Portrait photos are photos of a person's face that can reveal the character of the person, therefore the shooting exposure must be precise. In fact, the current portrait photos are not optimal because they do not consider the aspects of light and the correct shooting technique. Portrait photos can easily be done using window lighting techniques. This research was carried out on portrait photos with window lighting techniques produced from two different types of DSLR cameras. In the world of photography especially beginner photographers assume that the higher the level or class of the camera can produce better images. However, in the world of photography the results of good images are not solely produced by professional-class cameras, but by considering the exact exposure when shooting. Through this window lighting technique, researchers hope to find the essence and formula of making portrait photos that are of good quality and can be done by DSLR camera users. A good portrait photo, besides revealing a person's character also has a strong impact power.